Literature Coded for Marked Quick Response (American & British Studies Annual, 2013)
This paper examines the phenomenon of Quick Response codes (QR) and Augmented Reality markers (AR) in the context of contemporary literature. QR codes and AR markers, both traditionally represented as squares containing smaller black-and-white squares, require that the user firstly scans or photographs these images through his or her smartphones, computers, tablets or other digital devices, after which the content can be read, e.g. within websites. Several literary pieces have been based either on the concept of QR codes and markers or have implemented them for a particular reason (ranging from inviting the reader to discovery, hinting towards unveiling the content, referring to the tendencies of using QR codes in contemporary message-delivering or even marketing). This paper will concentrate primarily on two works of Quick Response Literature or Augmented Reality Literature, one Slovak (Joseph Juhász’s Urban Memoire) and one American (Amaranth Borsuk and Brad Bouse’s Between Page and Screen). These projects will be examined not only from the perspective of their formal attributes, but the poetics the works represent will also be analyzed in order to reveal their “real” “spirit/sprite.”
Keywords: augmented reality; QR codes; codes; AR books; electronic literature; digital media